2013
DOI: 10.1177/1545968313481280
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Early Physical Therapy in Severe Bell’s Palsy

Abstract: Physical therapy appears to be effective only in the more severe BP (baseline HB grade V/VI), whereas less severe BP (baseline HB grade IV) results in complete spontaneous recovery, regardless of physical therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
3
13

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(71 citation statements)
references
References 51 publications
(74 reference statements)
0
55
3
13
Order By: Relevance
“…Unfortunately, since this retrospective analysis was performed in the framework of a broader study on the management of Bell's palsy patients [Nicastri et al, ], no data on virus detection during the follow‐up are available. Perhaps the major limitation of this study is that the species of HHV‐6 detected in samples were not characterized, so further studies are needed to establish whether the association demonstrated is peculiar to one HHV‐6 species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, since this retrospective analysis was performed in the framework of a broader study on the management of Bell's palsy patients [Nicastri et al, ], no data on virus detection during the follow‐up are available. Perhaps the major limitation of this study is that the species of HHV‐6 detected in samples were not characterized, so further studies are needed to establish whether the association demonstrated is peculiar to one HHV‐6 species.…”
Section: Discussionmentioning
confidence: 99%
“…This study represents a further attempt to address this issue. In the framework of a broader project designed to gain new insights into the management of Bell's palsy patients [Nicastri et al, ], saliva and sera samples were collected from patients at the onset of paralysis symptoms. The presence of HSV‐1, VZV, and HHV‐6, and the serum antibody response were evaluated retrospectively.…”
Section: Introductionmentioning
confidence: 99%
“…In a randomized controlled trial (RCT) by Beurskens and colleagues, 112,113 patients with long-standing NFFP following BP, AN resection, VZV infection, and trauma receiving 3 months of comprehensive facial PT as opposed to being waitlisted demonstrated statistical improvements in patient-reported facial stiffness and FDI scores and quantitative assessment of lip length; however, no statistical benefit was seen in blinded expert-assessed FGS scores 12 months after therapy (level Ib). In the 2014 RCT by Pourmomeny and colleagues, 114 114 An RCT by Nicastri and colleagues 115 demonstrated that 74% of patients with BP presenting with severe to complete FFP (ie, HBG V/ VI) who received combination pharmacologic therapy (CPT) with prednisone and valacyclovir plus comprehensive PT within 10 days of symptom onset progressed to an HBG of I or II as assessed by 1 blinded expert within 6 months, compared with only 48% of those receiving CPT alone (adjusted P 5 .038) (level Ib). In summary, recent evidence supports the use of PT in acute FFP and long-standing NFFP.…”
Section: Physiotherapymentioning
confidence: 98%
“…Approximately 70% of all patients recover completely, and a higher percentage of improvement is achieved if corticosteroid therapy is prescribed [14,15]. Early physical rehabilitation is performed in severe grades of paresis [16]. Electrical nerve stimulation is a proposed method of accelerating recovery in patients through invoked muscle stimulation but, further studies will be required to assess clinical applicability [17,18].…”
Section: Discussionmentioning
confidence: 99%